2019
DOI: 10.1039/c9ob00028c
|View full text |Cite
|
Sign up to set email alerts
|

DFT mechanistic investigation into phenol dearomatization mediated by an iodine(iii) reagent

Abstract: The key intermediate for the oxidative dearomatization of phenols by phenyliodine(iii) diacetate (PIDA) was found to be a dearomatized phenolate species.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 51 publications
1
35
0
Order By: Relevance
“…According to thec alculations by Ariafard, this pathway is the most energetically favorable option in the PIDA-promoted addition of methanolt op-cresol, requiring to cross av iable % 24 kcal mol À1 barrier. [9] The incorporation of an iodine atom into the phenol ring, observed in some reactions with PIDA, also indirectly lends support to this mechanistic possibility. [10] Interestingly,n one of the mechanisms presented in Scheme 2c an fully account for all the observed characteristics of the reaction.…”
Section: Introductionmentioning
confidence: 85%
See 2 more Smart Citations
“…According to thec alculations by Ariafard, this pathway is the most energetically favorable option in the PIDA-promoted addition of methanolt op-cresol, requiring to cross av iable % 24 kcal mol À1 barrier. [9] The incorporation of an iodine atom into the phenol ring, observed in some reactions with PIDA, also indirectly lends support to this mechanistic possibility. [10] Interestingly,n one of the mechanisms presented in Scheme 2c an fully account for all the observed characteristics of the reaction.…”
Section: Introductionmentioning
confidence: 85%
“…In particular, the substantial rate enhancement with the increaseo fw ater content speaks strongly against the dissociative mechanism (Scheme 2, pathway 2), in which H 2 Oi se ngaged only after the rate-determining dissociation of intermediate A.T his is furtherr einforced by the large negative entropyo f activation,u nlikely for ad issociative process.T he measured experimental free energy barrier (22-23 kcal mol À1 )i sa lso considerably lower than that determined computationally for pathway 2( > 28 kcal mol À1 ), [7] but in agreement to those computed for pathways 1a nd 3( 21-24 kcal mol À1 ). [6,9] However,t he computational studies on the associativem echanisms have shown that in both the transition states of type TS1 and TS3 (Scheme 2, pathways 1a nd 3) for the barriers to be feasible, the attack of nucleophile must proceed with as imultaneous deprotonation by an acetate anion (not shown in the scheme). [6,9] This is, however,inconsistent with the lack of asolvent kinetic isotope effect upon the exchange of H 2 Of or D 2 O. Overall,t he data allows with high confidence to discard the pathways shown in Scheme 2a st he correct reactionm echanisms.…”
Section: Kineticsmentioning
confidence: 99%
See 1 more Smart Citation
“…The possibility of ligand exchange between HFIP and PIDA has been excluded and any altered reactivity to the oxidants is ruled out as the HFIP is a low nucleophilic solvent. [43][44][45][46][47] All of the above-mentioned study concerns the first step of the reaction, the SEO step, and seems to us in need for further understandings despite the subsequent steps that lead to the all trans cyclobutane ring are not considered, at least to the best of our knowledge, by other workers under these conditions. 26,[48][49][50] An important question that should be raised is the number of electrons to be transferred to the iodine reagent to initiate the reaction.…”
Section: Introductionmentioning
confidence: 99%
“…The possibility of ligand exchange between HFIP and PIDA has been excluded and any altered reactivity to the oxidants is ruled out as the HFIP is a low nucleophilic solvent. [43][44][45][46][47] All of the above-mentioned study concerns the first step of the reaction, the SEO step, and seems to us in need for further understandings, however, the subsequent steps that lead to the all trans cyclobutane ring are not considered, at least to the best of our knowledge, by other workers under these conditions. 26,[48][49][50] At this point, the reaction mechanism and reactivity of HVIR-mediate dimerization exclusively appears incomplete and warrants further attentions ( Figure 2).…”
Section: Introductionmentioning
confidence: 99%